Autologous Bone Marrow Mesenchymal Stem Cells Improve the Quality and Stability of Vascularized Flap Surgery of Irradiated Skin in Pigs. (18th May 2018) - Linard, Christine; Brachet, Michel; Strup-Perrot, Carine; L'homme, Bruno; Busson, Elodie; Squiban, Claire; Holler, Valerie; Bonneau, Michel; Lataillade, Jean-Jacques; Bey, Eric; Benderitter, Marc
Abstract : Cutaneous radiation syndrome has severe long-term health consequences. Because it causes an unpredictable course of inflammatory waves, conventional surgical treatment is ineffective and often leads to a fibronecrotic process. Data about the long-term stability of healed wounds, with neither inflammation nor resumption of fibrosis, are lacking. In this study, we investigated the effect of injections of local autologous bone marrow-derived mesenchymal stromal cells (BM-MSCs), combined with plastic surgery for skin necrosis, in a large-animal model. Three months after irradiation overexposure to the rump, minipigs were divided into three groups: one group treated by simple excision of the necrotic tissue, the second by vascularized-flap surgery, and the third by vascularized-flap surgery and local autologous BM-MSC injections. Three additional injections of the BM-MSCs were performed weekly for 3 weeks. The quality of cutaneous wound healing was examined 1 year post-treatment. The necrotic tissue excision induced a pathologic scar characterized by myofibroblasts, excessive collagen-1 deposits, and inadequate vascular density. The vascularized-flap surgery alone was accompanied by inadequate production of extracellular matrix (ECM) proteins (decorin, fibronectin); the low col1/col3 ratio, associated with persistent inflammatory nodules, and the loss of vascularization both attested to continued immaturity of the ECM. BM-MSC therapy combined with vascularized-flap surgery provided mature wound healing characterized by a col1/col3 ratio and decorin and fibronectin expression that were all similar to that of nonirradiated skin, with no inflammation, and vascular stability. In this preclinical model, vascularized flap surgery successfully and lastingly remodeled irradiated skin only when combined with BM-MSC therapy.